2009
DOI: 10.1002/qua.22088
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of nonlinear optical properties of oxocarbon derivatives

Abstract: ABSTRACT:In this work, first hyperpolarizability (β) and electronic spectra were obtained at ab initio and semiempirical levels of theory for mono-and bi-squarate derivatives. The results from our calculations suggest the investigated compounds as potential molecules for nonlinear optics (NLO). By means of the employed theoretical methodology, it was possible to identify structural aspects leading to enhancement of the NLO properties of the studied oxocarbons. Furthermore, a correlation between Hammett paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…The Hammett sigma constant is an empirical parameter for understanding the structure–property relationship among a series of derivatives with various substituents. Some linear or nonlinear correlations between the second‐order polarizabilities and σ values have been demonstrated by phthalocyanines,39 triazine derivatives,40, 41 metallabenzene‐based chromophores,42 azo dyes,43 and oxocarbon derivatives44. In Fig.…”
Section: Resultsmentioning
confidence: 89%
“…The Hammett sigma constant is an empirical parameter for understanding the structure–property relationship among a series of derivatives with various substituents. Some linear or nonlinear correlations between the second‐order polarizabilities and σ values have been demonstrated by phthalocyanines,39 triazine derivatives,40, 41 metallabenzene‐based chromophores,42 azo dyes,43 and oxocarbon derivatives44. In Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Here this global parameter covers a (2) [8,[42][43][44][45][46] have reported relationships among NLO quantities and some Hammett electronic parameters [32]. In a previous study [8], we found that β tot values of the 1,12-(para-) dicarba-closo-dodecarboranes push-pull compounds were enhanced by two orders of magnitude when compared to unsubstituted dodecarboranes.…”
Section: Resultsmentioning
confidence: 92%
“…It has also been shown that the nonlinear properties can be estimated with increased accuracy through the use of post‐Hatree–Fock (post‐HF) methods. However, semiempirical (Parametric Method 3 (PM3) and AM1), HF, and density functional theory (DFT) approaches have also been satisfactorily applied to relatively large molecules, for which more rigorous methods such as n th‐order Møller–Plesset perturbation theory (MPn) and coupled cluster (CC) are prohibitive 2, 21, 44, 45. The choice of the basis set also plays a role in the quality of the results.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, calculations using a large basis set with polarization and diffuse functions are required to reproduce the experimental magnitude of β 2, 44, 46. Nonetheless, several systematic theoretical studies indicate that the inclusion of an augmented set does not promote large differences in the β values for extended systems, with calculated values being in accordance with the experimental data even when medium‐size basis sets are used 2, 44–48. Furthermore, for very large molecules, such as those studied in this work, the small 6‐31G(d) basis set seems to be appropriate for structural determination as well as for calculation of the hyperpolarizability, because our main goal is to screen molecules with enhanced nonlinear responses within a specific class of compounds.…”
Section: Introductionmentioning
confidence: 99%